Решить уравнение : 5х-6-(3-2х)=5,5 ( с проверкой)

уляотличница уляотличница    3   19.06.2019 21:00    0

Ответы
danieldsha1234 danieldsha1234  15.07.2020 23:17
5х-6-(3-2х)=5,5
5х-6-3+2х=5,5
5х+2х=5,5+6+3
7х=14,5
х=14,5:7
х=145:70
х=2 целых 5/70
х=2 целых 1/14

Проверка
5\cdot 2 \frac{1}{14} -6-(3-2\cdot 2 \frac{1}{14})= 5\cdot \frac{29}{14} -6-(3-2\cdot \frac{29}{14})= \\ = \frac{145}{14} -6-(3- \frac{58}{14})= \\ \frac{145}{14} -9+ \frac{58}{14})=\frac{145+58}{14} -9=14,5-9=5,5
верно
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра